2017
DOI: 10.1002/prot.25358
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two tails: The importance of unstructured termini in the aggregation pathway of β2‐microglobulin

Abstract: The identification of intermediate states for folding and aggregation is important from a fundamental standpoint and for the design of novel therapeutic strategies targeted at conformational disorders. Protein human β2-microglobulin (HB2m) is classically associated with dialysis-related amyloidosis, but the single point mutant D76N was recently identified as the causative agent of a hereditary systemic amyloidosis affecting visceral organs. Here, we use D76N as a model system to explore the early stage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 73 publications
7
46
0
Order By: Relevance
“…The sub-unit 2 is involving residues belonging to complementary protein region respect to sub-unit 1. Our results are in line with previous modeling work at a more coarse grained level description [37], in which the authors studied dimers of D76N and put emphasis on the important role of DE loop for dimerization at physiological pH conditions, indicating as aggregation hot spots PHE56, TRP60, TYR63, ASP59, PHE62, TYR66 and also predicted as relevant residues LYS94 and TRP95. Based on a series of independent fully relaxed atomistic simulation of D76N dimers, we find a binding interface with strong presence of residues pertaining to DE loop and also residues from the C-term tail as predicted.…”
Section: D76n "Zipped" Dimersupporting
confidence: 91%
“…The sub-unit 2 is involving residues belonging to complementary protein region respect to sub-unit 1. Our results are in line with previous modeling work at a more coarse grained level description [37], in which the authors studied dimers of D76N and put emphasis on the important role of DE loop for dimerization at physiological pH conditions, indicating as aggregation hot spots PHE56, TRP60, TYR63, ASP59, PHE62, TYR66 and also predicted as relevant residues LYS94 and TRP95. Based on a series of independent fully relaxed atomistic simulation of D76N dimers, we find a binding interface with strong presence of residues pertaining to DE loop and also residues from the C-term tail as predicted.…”
Section: D76n "Zipped" Dimersupporting
confidence: 91%
“…Typically, these modified Gō potentials lead to domain-swapping (DS), a process of self-association in which two monomers exchange (one or more) identical parts of their structure (loops, helices or beta-strands) forming a bound dimer ( Ding et al, 2002 ). It is also possible to combine a full atomistic representation of the protein with the use of square-well discontinuous interaction potentials, including the Gō potential ( Estacio et al, 2012 , 2013 , 2014 ; Krobath et al, 2012 ; Loureiro et al, 2017 , 2019 ), and sample the conformational space with discontinuous molecular dynamics (DMD) simulations ( Chen and Dokholyan, 2005 ; Estacio et al, 2012 , 2013 , 2014 ; Krobath et al, 2012 ; Loureiro et al, 2017 , 2019 ), an efficient, event driven sampling scheme, which can also be combined with RE. Faísca et al have recently employed RE-DMD to compute the equilibrium folding space of the protein domain spcSH3 ( Krobath et al, 2012 ) and β2m to predict aggregation prone folding intermediates ( Estacio et al, 2014 ; Loureiro et al, 2017 , 2019 ).…”
Section: Computational Models and Techniques Used To Study β2m Aggregmentioning
confidence: 99%
“…In order to study the early phase of aggregation of β2m by means of molecular simulations, Faísca et al developed a methodology that combines and integrates data obtained from several computational tools mentioned above, namely, RE-DMD simulations, constant pH Molecular Dynamics (CpHMD) simulations, and protein-protein docking simulations ( Estacio et al, 2014 ; Loureiro et al, 2017 , 2019 ). This methodology does not consider the possibility of protein dimerization occurring concurrently and concomitantly with folding—a situation that could lead to DS dimers—but considers instead the scenario according to which protein–protein association occurs upon the formation of aggregation prone intermediate states en route to the native state.…”
Section: Computational Models and Techniques Used To Study β2m Aggregmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of intrinsic disorder in C- and N-terminal tails in formation of protein homo-oligomers were also highlighted in previous aggregation and amyloidogenesis studies. For example, analysis of the β2-microglobulin aggregation revealed that the enhanced dynamics of both tails caused more efficient aggregation of two protomers than aggregation in this protein form where the only C-terminal tail was flexible and even aggregation of previously discovered amyloidogenic mutants [ 66 , 67 ]. In the analysis of the dimerization of amyloidogenic variants of the α-spectrin SH3 domain (Spc-SH3), it was also discovered that the formation of partially folded intermediate where the N-terminal β1-strand is unstructured, and that a large part of the hydrophobic core is solvent exposed, is crucial for protein aggregation [ 68 ].…”
Section: Discussionmentioning
confidence: 99%